2020
DOI: 10.1007/978-3-030-47361-7_11
|View full text |Cite
|
Sign up to set email alerts
|

Error Reconciliation in Quantum Key Distribution Protocols

Abstract: Quantum Key Distribution (QKD) protocols allow the establishment of symmetric cryptographic keys up to a limited distance at limited rates. Due to optical misalignment, noise in quantum detectors, disturbance of the quantum channel or eavesdropping, an error key reconciliation technique is required to eliminate errors. This chapter analyses different key reconciliation techniques with a focus on communication and computing performance. We also briefly describe a new approach to key reconciliation techniques ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Unfortunately, it requires large block lengths ( ) [ 40 ]. Even more, decoding LDPC has larger computational and memory requirements than either Cascade or Winnow algorithms [ 41 ]. In contrast, our method does not require additional bits which reduces the coding rate.…”
Section: Communication Modelmentioning
confidence: 99%
“…Unfortunately, it requires large block lengths ( ) [ 40 ]. Even more, decoding LDPC has larger computational and memory requirements than either Cascade or Winnow algorithms [ 41 ]. In contrast, our method does not require additional bits which reduces the coding rate.…”
Section: Communication Modelmentioning
confidence: 99%
“…Shishniashvili et al [38] suggested a strategy to make use of the portions of the synchronized weight as a session key rather than the whole weight vector. In quantum key distribution protocols, Mehic et al [20] synchronization of two neural nets can serve as a reconciliation of errors as well. Niemiec [21] suggested the new approach of using the tree parity machine to address the mistakes in the quantum key distribution protocol during transmission.…”
Section: Related Workmentioning
confidence: 99%
“…Shishniashvili et al [29] recommended using components of the coordinated synaptic weight vector as a cryptographic key rather than a complete weight vector. In quantum key management procedures, coordination of two systems could be used to eliminate errors [12]. The complex-valued tree parity machine (CVTPM) was suggested by the authors in Dong and Huang [3], which utilizes complex numbers for all control parameters.…”
Section: Related Workmentioning
confidence: 99%